A prospective study of anti-vibration mechanism of microfluidic fuel cell via novel two-phase flow model. (1st March 2021) - Chen, Jingxian; Xu, Peihang; Lu, Jie; Ouyang, Tiancheng; Mo, Chunlan
Abstract: Microfluidic fuel cell is considered as a cleaner energy conversion device, and has potential commercial applications in portable electronic devices owing to its appreciable output power, prolonged work time and low emission. In a liquid-fed cell, however, a gaseous phase is generated, and the corresponding vibration effects have a considerable influence on performance. Thus, it is important to analyse the effects of the two-phase flow and vibration on the characteristics of a microfluidic fuel cell. A two-phase computational model is constructed for a microfluidic fuel cell employing a flow-over electrode. Multiple physical processes are coupled in the model, including the hydrokinetics, electrochemical reaction kinetics, species transport, vibration field, Euler-Euler model, and phase transfer. Results indicate that the aggravated vibration intensity and frequency lead to a negative effect comprising a critical fuel crossover and delayed gaseous discharge, resulting in the cell performance degradation. Besides, increasing the contact angle and flow rate contribute to a reduction in the gaseous volume fraction, but the latter considerably sacrifices fuel utilisation and exergy efficiency. The present work provides insights for the future development of anti-vibration elements and optimised cell design, and offers a reference for the sustainable practical application of microfluidic fuel cell. Graphical abstract: Image 1 Highlights: A two-phase model coupling vibration is developed for microfluidic fuel cell. Coupled mechanism of vibration and two-phase flow effects are investigated. Influences of factors on two-phase flow characteristic are compared. Fuel utilisation can be substantially improved at low flow rate.